Perbandingan Metode Maserasi dan Microwave-Assisted Extraction pada Daun Beluntas dengan Variasi Pelarut dan Uji Antioksidan: Comparison of Maceration and Microwave-Assisted Extraction on Beluntas Leaves with Variation of Solvent and Antioxidant Test - Utomo, Yudhi; Chairini, Nur; Asrori, Muhammad Roy (KOVALEN: Jurnal Riset Kimia, 2023)
Beluntas leaves (Pluchea indica L.) as Indonesian herbal plants contain secondary metabolites such as flavonoids. Beluntas leaf parts can be used as medicine. The content of secondary metabolites in Beluntas leaves acts as a natural antioxidant. Beluntas leaf extraction has not been optimal so far. Microwave assisted extraction can increase the yield. This research aims to study the effect of giving different types of solvents of extraction on Beluntas leaves on the levels of flavonoids and the resulting antioxidant activity, and determine the profile of Beluntas leaf extraction results based on comparative trials of the maceration method and MAE (microwave-assisted extraction). This research was conducted in 4 stages: (1) sample preparation of dried Beluntas leaves, (2) extraction by maceration with various types of solvents n-hexane, ethyl acetate, and 70% ethanol, (3) the characteristics of the flavonoid compounds, namely the qualitative test and the quantitative test with AlCl3, and (4) the measurement of antioxidant activity in Beluntas leaf extract using the DPPH method. The results of this study obtained a total flavonoid content of 4.23 mgQE/g which was the result of maceration of the ethyl acetate solvent extract (yield: 5.09%), and all Beluntas leaf extracts in ethyl acetate solvent were included in the category of very strong antioxidant activity with an IC50 value of 31.68 Î¼g/mL.